Metaphors in Himpunan Puisi Yang Melimpah dari Cucuran Atap Peribahasa by Marhalim Zaini - Sitepu, Chaterine Br; Rahayu, Sri (ARKA INSTITUTE, 2025)
This study aims to analyze, describe, and explain metaphors and types of metaphors in the collection Himpunan Puisi Yang Melimpah dari Cucuran Atap Peribahasa by Marhalim Zaini. In this poem, the types of metaphors are displayed, including anthropomorphic, animalistic, concrete to abstract, synesthesia. The problem in this study is to identify metaphors in the Himpunan Puisi Yang Melimpah dari Cucuran Atap Peribahasa by Marhalim Zaini. The theory used to analyze this study is Nurgiyantoro's theory. This study uses a qualitative approach with a descriptive method through literature studies. The data used in this study are in the form of texts or quotations and forms of metaphors. The data collection technique in this study uses hermeneutics, namely by reading and understanding the Himpunan Puisi yang Melimpah dari Cucuran Atap Peribahasa by Marhalim Zaini. Data analysis is carried out by grouping the reading results based on theory, then presenting them in the order of research problems in table form. The results of this study found 33 data in the form of metaphors consisting of 15 anthropomorphic metaphors, 3 animal metaphors, 10 concrete to abstract metaphors, and 5 synesthesia metaphors. Of the four metaphors, the anthropomorphic metaphor that often appears in the Himpunan Puisi yang Melimpah dari Cucuran Atap Peribahasa by Marhalim Zaini.